2018
DOI: 10.1002/sres.2513
|View full text |Cite
|
Sign up to set email alerts
|

Forms of Cooperation

Abstract: Investigations of cooperation often use totally different definitions, ranging from any mutual activities, via pursuing mutually stipulated goals, to altruistic services to others. To develop an overarching framework to order these definitions, the paper studies cooperation in the widest sense, understood as mutual activity towards mutually accepted goal values. It considers goal‐setting processes preceding cooperation, and the resulting different systems of goal values pursed and the related levels of utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, very often different things are understood by “cooperation” when referring to the necessities of cooperation: Investigations of cooperation often have a completely different understanding, ranging from any mutual activities, by pursuing mutually stipulated goals, to altruistic services to others. Nechansky (2018) developed an overarching framework to order these definitions and investigates into “cooperation in the widest sense, understood as mutual activity towards mutually accepted goal values. It considers goal‐setting processes preceding cooperation, and the resulting different systems of goal values pursed and the related levels of utility achieved by cooperating parties.…”
Section: Discussion: Freedom and Truthmentioning
confidence: 99%
See 3 more Smart Citations
“…However, very often different things are understood by “cooperation” when referring to the necessities of cooperation: Investigations of cooperation often have a completely different understanding, ranging from any mutual activities, by pursuing mutually stipulated goals, to altruistic services to others. Nechansky (2018) developed an overarching framework to order these definitions and investigates into “cooperation in the widest sense, understood as mutual activity towards mutually accepted goal values. It considers goal‐setting processes preceding cooperation, and the resulting different systems of goal values pursed and the related levels of utility achieved by cooperating parties.…”
Section: Discussion: Freedom and Truthmentioning
confidence: 99%
“…These different systems of goal‐values and achieved levels of utility provide a framework to distinguish eight forms of cooperation: They may express sharing ideals; agreement of equals or unequals; the uniting of cooperating units; the agreement of representatives; the restricted integration of newcomers; hierarchical top‐down subjection; or altruistic bottom‐up subordination. Finally, it is shown that market exchange neither applies nor leads to any of these forms of cooperation.” (Nechansky, 2018, Abstract).…”
Section: Discussion: Freedom and Truthmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite being highly desirable for human interaction, definitions of cooperation are quite different. They range from the obligation to be done by more than one person, to involving rational choices, when selfishness is not justified economically, lack of interest, or hierarchy (Nechansky, 2018).…”
Section: Cooperationmentioning
confidence: 99%